Academic Hardiness: Studi Literatur - Daphna Ivanka Latisha; Djamhoer, Temi Damayanti (UNISBA Press, 2024)
Abstract. This article is a literature review aimed at delving into the concept of academic hardiness in the academic context and as a form of stress management. A profound understanding of this concept is essential to depict the role of academic hardiness in facing challenges within the academic environment. Through literature analysis, this article seeks to provide a comprehensive overview of the significance of academic hardiness in understanding and managing stress in the academic domain. Abstrak. Artikel ini merupakan tinjauan literatur yang bertujuan untuk mendalami konsep academic hardiness dalam konteks akademis dan sebagai suatu bentuk manajemen stres. Pemahaman yang mendalam terhadap konsep ini menjadi kunci untuk menggambarkan peran academic hardiness dalam menghadapi tantangan di lingkungan akademis. Melalui analisis literatur, artikel ini bertujuan untuk memberikan gambaran yang komprehensif tentang arti penting academic hardiness dalam memahami dan mengelola stres di ranah akademis.